The Influences of Maghapurami Sri Prachin Philosophy Towards People In Prachinburi Province - Kingnara, Anuchit; Ponsen, Dr.Kitsuchin (Journal of Dhamma for Life, 2023)
The research article aims; 1. To study the Makhapurami Sri Prachin Traditional philosophy. 2. To study the Makhapurami Sri Prachin traditional philosophy that influences the way of life of the people in Prachinburi Province. 3. To analyse the Makhapurami Sri Prachin traditional philosophy. 4. To present the Maghapurami Sriprachin philosophy that influences the way of life of the people in Prachinburi. This research employs a multifaceted approach, combining the study of pertinent Tripitaka texts, relevant documents, and in-depth interviews. These interviews encompass three distinct groups: the first group consists of local residents (5 individuals), the second group comprises experts in Buddhism and philosophy (5 individuals), and the third group involves tourists (5 individuals), totalling 15 participants. The research employs content analysis to present a descriptive account of the gathered information. The research findings underscore the collaborative nature of organizing the festival, involving various sectors in Prachinburi Province, including the provincial administration, the Sangha, and local government entities. Furthermore, the research identifies that Makhapurami Sriprachin Traditional Philosophy profoundly influences the people of Prachinburi Province in three key dimensions: Spiritual Aspect: The philosophy instils Buddhist principles, promoting inner peace and tranquillity of the mind. Social Aspect: It impacts the overall societal fabric, fostering unity and cohesion in the community. Economic Aspect: The philosophy contributes to a harmonious and robust local economy. In conclusion, this research presents the essence of Makhapurami Sri Prachin Philosophy in the following manner: M = Mind: Reflecting the cultivation of a beautiful and peaceful state of mind. S = Society: Signifying the creation of a harmonious and united society. E = Economy: Indicating the development of a strong and prosperous local economy.